2015
DOI: 10.1159/000369161
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Determinants of Psychotic Symptoms in Alzheimer's Disease

Abstract: Aims: To investigate the relationship between psychotic symptoms and cognitive impairment in Alzheimer's disease (AD). Methods: A total of 108 subjects affected by AD were subdivided into subjects without delusions (ND), subjects with paranoid delusions (PD), subjects with delusional misidentifications (DM), subjects with both DM and PD (DM+PD), subjects with visual hallucinations (v-HALL), and subjects without visual hallucinations (N-HALL). Results: PD and ND subjects performed similarly on neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(71 reference statements)
1
7
1
Order By: Relevance
“…However, the frequency of hallucinations in CDR 2 patients was high, at 14.5%, suggesting that hallucinations occur more frequently in AD patients as dementia progresses. These results do not contradict previous findings that AD patients with visual hallucinations present with worse cognitive impairment [ 39 ] and visuospatial abilities [ 40 ] than do those without visual hallucinations. Hallucinations were observed in two of the seven FTLD patients with CDR 3 (28.6%) in this study, although the small number of patient means the reliability of this finding may be low.…”
Section: Discussionsupporting
confidence: 51%
“…However, the frequency of hallucinations in CDR 2 patients was high, at 14.5%, suggesting that hallucinations occur more frequently in AD patients as dementia progresses. These results do not contradict previous findings that AD patients with visual hallucinations present with worse cognitive impairment [ 39 ] and visuospatial abilities [ 40 ] than do those without visual hallucinations. Hallucinations were observed in two of the seven FTLD patients with CDR 3 (28.6%) in this study, although the small number of patient means the reliability of this finding may be low.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, the presence of PS was limited to a very weak number of participants, so this result should be interpreted with caution. Conversely to our findings, Quaranta et al showed that among 108 patients with moderate AD, the participants presenting PS had worse executive performances than patients without PS in univariate analysis 28 . However, the patients with PS had a global greater cognitive impairment and a more severe disease stage than ones without PS.…”
Section: Discussioncontrasting
confidence: 99%
“…Delusional subtype, such as persecutory delusions or misidentification delusions, may additionally have separate neurobiology. For instance, patients with misidentification delusions may have more advanced decline compared to patients with persecutory delusions [61, 62]. Lastly, the subgroups were very modest in size, especially in the AD+H group with only 83 subjects.…”
Section: Discussionmentioning
confidence: 99%